Pars Plana Vitrectomy Management of Dropped Nucleus or Dropped IOL After Cataract Surgery at Cipto Mangunkusumo National General Hospital in Indonesia - Karniela Ayuni Putri; Ari Djatikusumo; Andi Arus Victor; Gitalisa Andayani; Anggun Rama Yudantha; Mario Marbungaran Hutapea; Filza Amara Kamila Harlena (International Journal of Retina, 2026)
Introduction: Dropped nucleus or dropped intraocular lens (IOL) are two potential complications of cataract surgery that threaten visual acuity and require further intervention. The standard procedure for both conditions is pars plana vitrectomy (PPV). This retrospective study aimed to describe the demographic, clinical characteristics, and treatment outcomes of dropped nucleus or dropped IOL cases after PPV at Cipto Mangunkusumo National General Hospital between January 2023 and December 2024. Methods: This retrospective descriptive study analyzed the medical records of 120 patients diagnosed with dropped nucleus or dropped IOL who underwent PPV. Data collected included demographics, visual acuity (logMAR), procedure characteristics, and postoperative complications. They were then analyzed using SPSS. Result: Out of 120 total cases (63 dropped nucleus, 57 dropped IOL), the patients were predominantly male with a mean age of ≈60 years old. Mean preoperative visual acuity was poor (1.84 logMAR for dropped nucleus, 1.81 logMAR for dropped IOL). ​​The primary surgical management for dropped nucleus was vitrectomy with endofragmentation (≈53% of total cases) and for dropped IOL, the main procedure was vitrectomy with IOL explantation (≈41% of total cases). The management of most dropped nucleus cases (65.07%) was done within ≤1 month, while dropped IOL cases were often delayed. Postoperative complications were infrequent (≈92% complication-free), with increased IOP (4.76–5.26%) and retinal detachment (1.58–1.75%) being the most common. Mean postoperative visual acuity showed improvement for both groups (1.81 logMAR for dropped nucleus and 1.77 logMAR for dropped IOL). Conclusion: PPV with appropriate adjunct procedures, such as endofragmentation or IOL explantation, is an effective and necessary treatment for dropped nucleus or dropped IOL, leading to an improvement in postoperative visual acuity outcomes with minimal to no postoperative complications.